Hyperuricaemia and risk of nonalcoholic fatty liver disease: A meta-analysis - Karn Wijarnpreecha (2018)
© 2016 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Background: The association between hyperuricaemia and nonalcoholic fatty liver disease (NAFLD), one of the leading causes of cirrhosis worldwide, has been demonstrated in recent epidemiological studies. This meta-analysis was conducted to summarize all available data and to estimate the risk of NAFLD among subjects with hyperuricaemia. Methods: Comprehensive literature review was conducted using MEDLINE and EMBASE database through August 2016 to identify studies that compared the risk of NAFLD among subjects with hyperuricaemia vs those with normal uric acid level. Effect estimates from individual study were extracted and combined together using random-effect, generic inverse variance method of DerSimonian and Laird. Results: Twenty-five studies met the eligibility criteria and were included in the meta-analysis. The risk of NAFLD in subjects with hyperuricaemia was significantly higher than subjects with normal uric acid level with the pooled odds ratio (OR) of 1.97 (95% confidence interval (CI), 1.69-2.29). The heterogeneity between studies of the overall analysis was high with an I2of 87%. Subgroup analysis based on 11 studies that provided data on males subgroup and nine studies that provided data on females subgroup showed that the risk was significantly increased for both sexes with pooled OR of 1.64 (95% CI, 1.40-1.93) among males and pooled OR of 2.21 (95% CI, 1.85-2.64) among females. Conclusions: A significantly increased risk of NAFLD among patients with hyperuricaemia was demonstrated in this meta-analysis. Further studies are required to establish the role of uric acid in the pathogenesis of NAFLD.